Genome-wide identification of YABBY genes in three Cymbidium species and expression patterns in C. ensifolium (Orchidaceae) - Wang, Qian-Qian; Li, Yuan-Yuan; Chen, Jiating; Zhu, Meng-Jia; Liu, Xuedie; Zhou, Zhuang; Zhang, Diyang; Liu, Zhong-Jian; Lan, Siren (Frontiers in Plant Science, 2022)
Members of the YABBY gene family play significant roles in lamina development in cotyledons, floral organs, and other lateral organs. The Orchidaceae family is one of the largest angiosperm groups. Some YABBYs have been reported in Orchidaceae. However, the function of YABBY genes in Cymbidium is currently unknown. In this study, 24 YABBY genes were identified in Cymbidium ensifolium, C. goeringii, and C. sinense. We analysed the conserved domains and motifs, the phylogenetic relationships, chromosome distribution, collinear correlation, and cis-elements of these three species. We also analysed expression patterns of C. ensifolium and C. goeringii. Phylogenetic relationships analysis indicated that 24 YABBY genes were clustered in four groups, INO, CRC/DL, YAB2, and YAB3/FIL. For most YABBY genes, the zinc finger domain was located near the N-terminus and the helix-loop-helix domain (YABBY domain) near the C-terminus. Chromosomal location analysis results suggested that only C. goeringii YABBY has tandem repeat genes. Almost all the YABBY genes displayed corresponding one-to-one relationships in the syntenic relationships analysis. Cis-elements analysis indicated that most elements were clustered in light-responsive elements, followed by MeJA-responsive elements. Expression patterns showed that YAB2 genes have high expression in floral organs. RT-qPCR analysis showed high expression of CeYAB3 in lip, petal, and gynostemium. CeCRC and CeYAB2.2 were highly expressed in gynostemium. These findings provide valuable information of YABBY genes in Cymbidium species and the function in Orchidaceae.